2013
DOI: 10.1093/hmg/ddt520
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation and modulation of NF B-related genes in celiac disease: uncovered aspects of gut mucosal inflammation

Abstract: It is known that the NFκB route is constitutively upregulated in celiac disease (CD), an immune-mediated disorder of the gut caused by intolerance to ingested gluten. Our aim was to scrutinize the expression patterns of several of the most biologically relevant components of the NFκB route in intestinal biopsies from active and treated patients and after in vitro gliadin challenge, and to assess normalization of the expression using an inhibitor of the MALT1 paracaspase. The expression of 93 NFκB genes was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 51 publications
(55 reference statements)
5
61
0
1
Order By: Relevance
“…1D and fig. S5, D and E), consistent with the observation that NF-κB is constitutively active in the mucosa of patients with CeD (4). The lack of Myd88 did not affect Il18rap induction but does affect IL-12 (Fig.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…1D and fig. S5, D and E), consistent with the observation that NF-κB is constitutively active in the mucosa of patients with CeD (4). The lack of Myd88 did not affect Il18rap induction but does affect IL-12 (Fig.…”
supporting
confidence: 89%
“…Long noncoding RNAs (lncRNAs) represent a large portion of noncoding regions across the genome (1); however, the link between the GWAS phenotype–related loci on lncRNA expression or function—and the implications for disease—remain uncharacterized (2, 3). Celiac disease (CeD) is a chronic, immune-mediated intestinal disorder that is caused by intolerance to ingested gluten and develops in genetically susceptible individuals (4, 5). Recent studies have revealed 39 non– human lymphocyte antigen regions associated with a risk of CeD development, including many in noncoding regions (68).…”
mentioning
confidence: 99%
“…Fern andezJim enez et al [121] studied the expression in intestinal biopsies of 93 NFkB-related genes and confirmed the activation of a considerable fraction of those genes in CD. Notoriously, genes of the core of the pathway were increased in the group of constitutively altered genes (independently of the patients were following a GFD or not), in contrast to the increased number of more peripheral genes observed in patients with active disease.…”
Section: Insights From Non-mhc Genetic Variantsmentioning
confidence: 88%
“…Correlation between the expression of a subset of differentially expressed long non-coding genes and their closest genes was performed as previously described using Pearson correlations [54]. …”
Section: Methodsmentioning
confidence: 99%